サイナスリフトの隣在歯への影響について - 小川 優; 清川 宗克; 石井 良明; NAKABAYASHI Atsushi; 鈴木 崇夫; 三上 格; 新井田 淳; 賀来 亨 (Journal of Japanese Society of Oral Implantology, 2004)
A 45-year-old male visited our clinic with a chief complaint of masticatory disturbance due to edentulism of the left maxillary molars and the right second maxillary premolar, and due to marginal problems around the left mandibular second molar. Because of bone loss at the edentulous left posterior maxilla, inadequate bone was available for implant anchorage. A sinus grafting was indicated in this patient. Bone was harvested from the symphyseal area and grafted to the left maxillary sinus floor after a sinus lift procedure. At 11 months after an adequate amount of bone material was confirmed, the placement of an endosseous implant (8 mm in length) was performed. Just after the placement of the implant, a periapical radiolucent lesion of the left maxillary second premolar adjacent to the procedure area was noted.The patient had no symptoms of any pain. The affected tooth had been checked regularly for devitalization by use of an instrument for pulp diagnosis and was thought to be vital. Following a 6 month-period of integration, the implant was uncovered and an abutment was placed and loaded with a fixed prosthesis. Incorporation of the implant was evaluated by clinical and radiographical examinations just after the abutment was placed and every year thereafter. An internal dental fistula appeared at the buccal gingival mucosa approximately five years after the sinus grafting, which was consistent with the periapical radiolucent lesion. The affected tooth was checked during a regular examination with the use of an instrument for pulp diagnosis and judged to be devitalized. Endodontic therapy on the devitalized tooth was performed. Placing the sinus lift augmentation too close to an apically natural tooth may result in adevitalized tooth. Therefore, a follow-up of the placement of an implant combined with sinus lift augmentation at regular intervals is very important.